Induction of microRNA-10a using retinoic acid receptor-α and retinoid x receptor-α agonists inhibits atherosclerotic lesion formation. (April 2018) - Lee, Ding-Yu; Yang, Tung-Lin; Huang, Yi-Hsuan; Lee, Chih-I.; Chen, Li-Jing; Shih, Yu-Tsung; Wei, Shu-Yi; Wang, Wei-Li; Wu, Chih-Cheng; Chiu, Jeng-Jiann
Abstract: Background and aims: MicroRNA (miR)-10a is a shear-regulated miR with the lowest expression in vascular endothelial cells (ECs) in athero-susceptible regions with oscillatory shear stress (OS). The aim of this study is to elucidate the relationship between EC miR-10a and atherosclerosis and develop a hemodynamics-based strategy for atherosclerosis treatment. Methods: A combination of in vitro flow system and in vivo experimental animals was used to examine the functional roles of EC miR-10a and its clinical applications in atherosclerosis. Results: En face staining showed that EC miR-10a is down-regulated in the inner curvature (OS region) of aortic arch in rats. Co-administration with retinoic acid receptor-α (RARα)- and retinoid X receptor-α (RXRα)-specific agonists rescued EC miR-10a expression in this OS region. These effects of OS and RARα/RXRα-specific agonists on EC miR-10a expression were confirmed by the in vitro flow system, and were modulated by the RARα-histone deacetylases complex, with the consequent modulation in the downstream GATA6/vascular cell adhesion molecule (VCAM)-1 signaling cascade. Animal studies showed that miR-10a levels are decreased in both aortic endothelium of atherosclerotic lesions and blood plasma from apolipoprotein E-deficient ( ApoE −/− ) mice. In vivo induction of EC miR-10a by administration of RARα/RXRα-specific agonists protects ApoE −/− mice from atherosclerosis through inhibition of GATA6/VCAM-1 signaling and inflammatory cell infiltration. Conclusions: Our findings indicate that down-regulation of miR-10a in aortic endothelium and blood serum is associated with atherosclerosis, and miR-10a has potential to be developed as diagnostic molecule for atherosclerosis. Moreover, EC miR-10a induction by RARα/RXRα-specific agonists is a potential hemodynamics-based strategy for atherosclerosis treatment. Highlights: Decreased miR-10a levels in serum and ECs are associated with atherosclerosis. miR-10a is a promising diagnostic biomarker for atherosclerosis. RARα/RXRα-specific agonists up-regulate EC miR-10a to inhibit atherosclerosis.